Anatomical description and clinical significance of unilateral triheaded sternocleidomastoid muscle - Goswami, Preeti; Yadav, Yogesh; V, Chakradhar (International Journal of Research in Medical Sciences, 2017)
Objective of this report is to observe and report unusual pattern of origin of sternal and clavicular heads of Sternocleidomastoid (SCM). An embryological insight into the possible causes for present anomaly is elucidated. The neck region of an adult male cadaver during gross anatomy teaching program. An abnormal Sternocleidomastoid (SCM) was observed while dissecting the neck region of an adult. Additional clavicular head of SCM muscle were found on the right side. The accessory clavicular head coursed deep to the sternal head whereas the some fibres of main clavicular head joined the accessory belly and together they fused with the main sternal head of SCM. There was another slip arising from sternal head and merge with deep cervical fascia near base of mandible. The topographical anatomy of SCM is extremely important, particularly because it serves as a useful surgical landmark and its relation to crucial neuro-vascular structures of the neck. The usage of SCM in reconstruction operations for covering defects is discussed. A detailed knowledge of the anatomy of SCM proves vital for radiological studies of the neck.